Extreme Subwavelength Magnetoelastic Electromagnetic Antenna Implemented with Multiferroic Nanomagnets. Issue 8 (24th June 2020) - Drobitch, Justine Lynn; De, Anulekha; Dutta, K.; Pal, Pratap Kumar; Adhikari, Arundhati; Barman, Anjan; Bandyopadhyay, Supriyo
Abstract: Antennas typically have emission/radiation efficiencies bounded by A /λ 2 ( A < λ 2 ) where A is the emitting area and λ is the emitted wavelength. That makes it challenging to miniaturize antennas to extreme subwavelength dimensions without severely compromising their efficiencies. To overcome this challenge, an electromagnetic (EM) antenna is actuated with a surface acoustic wave (SAW) whose wavelength is about five orders of magnitude smaller than the EM wavelength at the same frequency. This allows to implement an extreme subwavelength EM antenna, radiating an EM wave of wavelength λ = 2 m, whose emitting area is ≈10 −8 m 2 ( A /λ 2 = 2.5 × 10 −9 ), and whose measured radiation efficiency exceeds the A /λ 2 limit by over 10 5 . The antenna consists of magnetostrictive nanomagnets deposited on a piezoelectric substrate. A SAW launched in the substrate with an alternating electrical voltage periodically strains the nanomagnets and rotates their magnetizations owing to the Villari effect. The oscillating magnetizations emit EM waves at the frequency of the SAW. These extreme subwavelength antennas that radiate with efficiencies a few orders of magnitude larger than the A /λ 2 limit allow drastic miniaturization of communication systems. Abstract : An extreme subwavelength antenna is implemented by exciting magnetostrictive nanomagnets delineated on a piezoelectric substrate with a surface acoustic wave. The antenna radiation efficiency exceeds the ( A /λ) 2 limit by more than five orders of magnitude where A is the surface emitting area and λ is the wavelength of emitted radiation, thereby opening the door to drastic miniaturization of antennas.